2018
DOI: 10.1007/s11894-018-0646-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Endoscopic Procedure Complications

Abstract: Significant complications of endoscopy requiring emergency department or inpatient admission in otherwise healthy children are unusual, but more common with therapeutic procedures; risk from procedures increases incrementally with preoperative coexisting conditions. Duodenal hematoma is predominantly a pediatric endoscopic complication and is more likely in hematology-oncology patients. Air embolism is a well-defined endoscopic retrograde cholangiopancreatography (ERCP) complication in adults and is likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 82 publications
0
17
0
2
Order By: Relevance
“…and Tringali et al . also reported in 2018 and 2016, respectively, an adverse event rate of 0.65% associated with endoscopic examination 14,15 . Thakkar et al .…”
Section: Discussionmentioning
confidence: 87%
“…and Tringali et al . also reported in 2018 and 2016, respectively, an adverse event rate of 0.65% associated with endoscopic examination 14,15 . Thakkar et al .…”
Section: Discussionmentioning
confidence: 87%
“…Durante la realización de una EDS pueden presentarse complicaciones como perforación y sangrado 3 , las cuales son infrecuentes en manos de personal entrenado y cuando se presentan están relacionadas principalmente con procedimientos terapéuticos y en pacientes con condiciones médicas preexistentes 29 , similar a nuestros hallazgos. Shrestha S. y cols.…”
Section: Complicacionesunclassified
“…y cols. reportaron una tasa de complicaciones del 0,7% en los procedimientos terapéuticos 29,30 . La tasa de complicaciones anestésicas es < 2% y los pacientes con comorbilidades son los que tienen mayor riesgo 31 , hallazgos que concuerdan con nuestra población de estudio tanto en la tasa de presentación como las características clínicas de los pacientes afectados.…”
Section: Complicacionesunclassified
“…Before surgery, ERCP can improve drainage, solve complications, and allow subsequent safe surgery. Post-ERCP pancreatitis was the main complication that was considered[ 17 - 19 ]. Zeng et al [ 16 ] reported that it was diagnosed according to the following criteria: Presence of pancreatic pain persisting for at least 24 h and serum amylase level at least 3 times higher than the normal level after ERCP.…”
Section: Diagnostic Imaging Techniquesmentioning
confidence: 99%